A retrospective analysis of maize performance under low nitrogen stress conditions in sub-Saharan Africa - Gokoma, S.; Kamutando, C.N.; Siwela, M.; Derera, J. (Frontiers Media, 2025)
Introduction: Fertilizer use in sub-Saharan Africa (SSA) is the lowest in theworld and has stagnated. Consequently low nitrogen (N) stress is one of the principal constraints to maize yields in this region. Therefore improving nitrogen use efficiency of maize varieties will result in higher nitrogen recovery rates, leading to less leaching of nitrogen as well as loss through nitrification and ammonification. This study aimed to: 1) Investigate the relationship between grain yield under low N and optimal conditions; and 2) Establish the level of variability in low N tolerance among elite Eastern and Southern African (ESA) maize varieties.